The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/app.48713
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic, tough composite core/shell PCL/PVA‐GEL nanofibers for biomedical application

Abstract: Emulsion electrospinning using natural and synthetic polymers, including two dissimilar materials is a promising technique for nanofibers fabrication in a core/shell configuration for tissue engineering, controlled or sustained drug delivery and dressing applications. In this study, we designed and fabricated core/shell nanofibers based on polycaprolactone (PCL) as core material and poly(vinyl alcohol) (PVA)‐gelatin (GEL) blend as shell materials (PCL/PVA‐GEL) to achieve high mechanical properties, good cell g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The decrease in the viscosity of the T4 sample indicates a decrease in the interfacial energy between the droplets due to, for example, coalescence or flocculation. This decrease indirectly indicates that the emulsion started to lose stability [ 47 ]. One hour after preparation, this drop in viscosity is more likely to be due to the decomposition of the micelles than to the miscibility of the water and oil phases or the volume fraction of the water phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the viscosity of the T4 sample indicates a decrease in the interfacial energy between the droplets due to, for example, coalescence or flocculation. This decrease indirectly indicates that the emulsion started to lose stability [ 47 ]. One hour after preparation, this drop in viscosity is more likely to be due to the decomposition of the micelles than to the miscibility of the water and oil phases or the volume fraction of the water phase.…”
Section: Discussionmentioning
confidence: 99%
“…Akbarzadeh et al obtained PCL/PVA-GEL core/shell nanofibers, which induced adhesion of the L929 fibroblasts. Biological studies showed high cell viability (above 80%) after 24 h and 48 h incubation, spindle-like morphology, and no signs of damage (cells debris) [ 47 ]. Basar et al, who also conducted research on the same type of cells, reported a positive effect of the emulsion electrospun PCL/gelatin fibers containing ketoprofen on the viability ant phenotype of the L929 fibroblasts [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The porosity of DPS was determined using the liquid displacement technique [27]. The scaffold (W d , dry weight) was submerged in ethanol for 30 min and the weight of wet samples was calculated W 1 .…”
Section: Porositymentioning
confidence: 99%
“…PCL has also been combined with various polymers to create blended fibrous scaffolds with enhanced mechanical properties and cell attachment capabilities. Akbarzadeh et al fabricated a biphasic fibrous matrix composed of PCL, PVA and gelatin which demonstrated fibroblast interaction and enhanced cell proliferation within 24 hours [441] whilst Ghasemkhah et al developed gelatin/PCL scaffolds which proved to be promising protein delivery systems to aid in the tissue regeneration process [442].…”
Section: Electrospinningmentioning
confidence: 99%